Prevalence and correlates of periodontitis among Kenyan women planning to conceive - Brenda Oyaro; Erica Lokken; Hudson Alumera; Shahid Hussein; Barbra Richardson; Kishorchandra Mandaliya; Walter Jaoko; John Kinuthia; Elizabeth Dimba; Arthur Kemoli; R. Scott McClelland (BMC, 2022)
Abstract Background Periodontitis has been associated with adverse pregnancy outcomes. Little is known about the burden and risk factors for periodontitis among reproductive age women in sub-Saharan Africa. This analysis aimed to determine the prevalence and correlates of periodontitis among Kenyan women planning to conceive. Methods HIV-seronegative, reproductive-age women who were planning to conceive were enrolled and underwent a periodontal examination. Following the US Centers for Disease Control and Prevention clinical case definitions, the presence and severity of periodontitis was determined by establishing the level of clinical periodontal attachment loss and graded in three categories: no/mild, moderate, and severe. Secondary outcomes included the scores on the Gingival Index and Decayed, Missing, and Filled Teeth (DMFT) Index. Correlates of periodontitis were examined using univariable and multivariable logistic regression. Results Of the 647 women in the study, 84% (n = 541) had no/mild periodontitis, 15% (n = 97) had moderate periodontitis, and 1% (n = 9) had severe periodontitis. Mild gingivitis was present in 61% (n = 396) of women, while 27% (n = 176) had moderate gingivitis, and 1% (n = 9) had severe gingivitis. The majority (75%, n = 487) of women had a DMFT index in the very low range (score < 5). Periodontitis was observed in 12% (12/101) of nulliparous women compared to 13% (36/286) of women with one prior delivery (prevalence ratio [PR] 1.03, 95% confidence interval [95% CI] 0.57-1.96), 21% (36/170) of women with two prior deliveries (PR 1.78, 95% CI 0.97-3.26), and 24% (22/90) of women with 3 or more prior deliveries (PR 2.06, 95% CI 1.08-3.92). Conclusion This study demonstrated a substantial prevalence of moderate-severe periodontitis among women planning to conceive in Kenya. These results highlight the need to address the oral care needs of reproductive age women, particularly those with multiple prior pregnancies.